Influence of perceived equity, job enrichment, and burnout among educators in Indian private universities on job satisfaction and the desire to quit - Annamalai, Sumathi (Frontiers in Education, 2022)
Desire to quit converts into actual attrition if left unattended. Also, job satisfaction of employees strongly influences their desire to stay or leave. Several individual and organizational factors affect job satisfaction level, all of which must be thoroughly analyzed to curb both desire to quit and attrition. The current study tests a model associating perceived equity, job enrichment, and burnout impacting job satisfaction and desire to quit of educators employed in private universities in India. Data was collected from 272 university faculty members using 5 scales, namely, job enrichment, perceived equity, employee burnout, job satisfaction and intention to leave and was analyzed using AMOS 17. Results show that perceived equity has a positive influence on job satisfaction (hypothesis 2), job enrichment positively affects job satisfaction (hypothesis 3), burnout negatively influences job satisfaction (hypothesis 4), and job satisfaction negatively affects desire to leave (hypothesis 1). Perceived equity, burnout and job satisfaction was found to mediate the association between job enrichment and desire to leave. The results indicate that private universities must focus on job satisfaction to reduce employees’ desire to quit, thereby reducing the attrition level, which is currently a severe problem with both financial and nonfinancial consequences to universities. From the results it can be seen job enrichment has acted as a mediator to influence job satisfaction of employees. Future research can explore on HR practices contributing to high job enrichment and this study would have considerable practical implications.